Kalazion - Syarifah Rohaya; Rizqa Shafrina (Lembaga Pengembangan Kinerja Dosen, 2023)
Chalazion is granulomatous inflammation with lipogranuloma or chronic non-infectious inflammation of the eyelids, in the form of nodules formed by inflammation and obstruction of the Meibomian Tarsal or Zeis glands. This chalazion often occurs in all age groups, but is more common in adults than children, and affects men and women equally. A chalazion usually appears as a painless swelling of the eyelid that has been present for weeks to months, which can cause cosmetic deformity in the patient. The priority management of chalazion to reduce existing complaints is conservative management. Some methods for conservative management in cases of chalazion include warm compresses, cleaning the eyelids with baby shampoo, and massaging the eyelids. If conservative management fails, patients can be treated with pharmacotherapy or surgery